An exploration of product advantage and its antecedents in SMEs. Issue 1 (12th February 2018) - Healy, Brian; O'Dwyer, Michele; Ledwith, Ann
Abstract : Purpose: Product advantage is consistently identified as the most important product characteristic in explaining the adoption and success of a new product. In small- and medium-size enterprises (SMEs), in particular, improving new product performance is critical in supporting SME survival and growth. Given that SMEs are a vital component of most economies improving their ability to effectively launch new products is an essential activity for sustainability. However, although literature illustrates that developing products with high levels of product advantage and new product development is advantageous, few studies have explored product advantage activities in SMEs and consequently research on product advantage is over-reliant on large firm studies. Given the specific resource constraints which challenge SME new product development (i.e. financial, expertise, access to networks etc.) context-specific research is critical. The purpose of this paper is to address these gaps in literature by exploring the product advantage activities in four manufacturing SMEs actively engaged in product development. Design/methodology/approach: The research question centres on exploring the antecedents of product advantage in SMEs (market uncertainties, competitive intensity, resource uncertainties and technological uncertainties) in the context of multi-dimensional perspective of product advantage (consisting of product innovativeness, product superiority and product meaningfulness). A qualitative interpretivist approach was used to explore the research question exploring the antecedents to, and nature of, product advantage in SMEs. Case studies were used to inductively and holistically view SMEs in their entirety, this approach facilitated in-depth understanding of the reality of the SME and allowed for the interpretation of the SMEs owner/managers perspectives on product advantage. Findings: The empirical findings suggest that the most significant antecedent of product advantage in the case SMEs was competitive intensity followed by technology uncertainty and resource uncertainty and then market uncertainty. Product advantage was found to be strongly based on product meaningfulness with elements of product innovativeness and product superiority also defining their perspective of product advantage. Research limitations/implications: There are several implications for SME owner/managers arising from this study. In the context of these findings, SMEs need to carefully consider three issues in supporting their new product development: first, their dependence on letting existing customers drives their new product development; second, owner/manager perceptions of product advantage are focused on delivering guaranteed sales, this focus nurtures incremental continuous product development rather than radical discontinuous innovation. While this strategy is low risk and supports SME sustainability, it could lead to less ambitious innovation strategies and slower growth for SMEs; third, antecedents of product advantage such as competitive intensity, technology uncertainty and resource uncertainty and market uncertainty need to carefully managed. Originality/value: This study illustrates the complex nature of the antecedents and nature of product advantage in SMEs. The study provides insight into the product advantage characteristics that SMEs consider important in the development of new products. Different elements of each of the three product advantage constructs (product meaningfulness, product superiority and customer meaningfulness) are considered important under different conditions. Throughout this analysis, market needs and wants, technology, competitors and resources emerged as the defining conditions upon which product advantage decisions are based. More specifically knowledge regarding the market, technology, competition and the availability of resources dictated the type and levels of advantages that were presented in new products.